PENILAIAN KINERJA KEUANGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED PADA PT SEMEN TONASA (PERSERO) - Utomo, Dini Fauziyah; Sahabuddin, Romansyah; Nurman, Nurman (DECISION : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to evaluate the performance of PT Semen Tonasa (Persero) for the 2016-2020 period using the Economic Value Added method. The population and sample in this study are all accounts in the financial statements of PT Semen Tonasa (Persero) during the 2016-2020 period. This study uses data collection techniques with the documentation method, by collecting available data in the form of financial reports obtained from the company PT Semen Tonasa (Persero) for the 2016-2020 period. The data obtained were analyzed using several processing and then measured using the Economic Value Added method. The results of the study concluded that the Economic Value Added of PT Semen Tonasa (Persero) has a positive value, namely the EVA value > 0. This indicates that there is a value added process in the company.